Relationship between genetically determined telomere length and glioma risk. Issue 2 (3rd September 2021) - Saunders, Charlie N; Kinnersley, Ben; Culliford, Richard; Cornish, Alex J; Law, Philip J; Houlston, Richard S
Abstract: Background: Telomere maintenance is increasingly recognized as being fundamental to glioma oncogenesis with longer leukocyte telomere length (LTL) reported to increase risk of glioma. To gain further insight into the relationship between telomere genetics and risk of glioma, we conducted several complementary analyses, using genome-wide association studies data on LTL (78 592 individuals) and glioma (12 488 cases and 18 169 controls). Methods: We performed both classical and summary Mendelian randomization (SMR), coupled with heterogeneity in dependent instruments tests, at genome-wide significant LTL loci to examine if an association was mediated by the same causal variant in glioma. To prioritize genes underscoring glioma-LTL associations, we analyzed gene expression and DNA methylation data. Results: Genetically increased LTL was significantly associated with increased glioma risk, random-effects inverse variance weighted ORs per 1 SD unit increase in the putative risk factor (odds ratio [OR]SD ) 4.79 (95% confidence interval: 2.11-10.85; P = 1.76 × 10 −4 ). SMR confirmed the previously reported LTL associations at 3q26.2 ( TERC ; P SMR = 1.33 × 10 −5 ), 5p15.33 ( TERT ; P SMR = 9.80 × 10 −27 ), 10q24.33 ( STN1 alias OBFC1 ; P SMR = 4.31 × 10 −5 ), and 20q13.3 ( STMN3/RTEL1 ; P SMR = 2.47 × 10 −4 ) glioma risk loci. Our analysis implicates variation at 1q42.12 ( P SMR = 1.55 × 10 −2 ), 6p21.3 ( P SMR = 9.76 × 10 −3 ), 6p22.2 ( P SMR = 5.45 × 10 −3 ), 7q31.33 ( P SMR = 6.52 × 10 −3 ), and 11q22.3 ( P SMR = 8.89 × 10 −4 ) as risk factors for glioma risk. While complicated by patterns of linkage disequilibrium, genetic variation involving PARP1, PRRC2A, CARMIL1, POT1, and ATM-NPAT1 was implicated in the etiology of glioma. Conclusions: These observations extend the role of telomere-related genes in the development of glioma.